Board meetings, committee structure, and firm value - Brick, Ivan E.; Chidambaran, N.K. (Journal of Corporate Finance, 2010)
In this study, we examine the determinants of board monitoring activity and its impact on firm value for a broad panel of firms over a six-year period from 1999 to 2005. During this period, Congress and the exchanges promulgated regulations that increased pressure upon firms for more independent and active boards. Economists have debated whether board activity and externally imposed regulations benefit or harm firms. We develop and examine several proxies for board monitoring and examine the relationship between board monitoring activity, firm characteristics, and firm value in a structural equation framework. One set of our proxies is based on the number of annual board and Audit Committee meetings. We show that prior performance, firm characteristics and governance characteristics are important determinants of board activity. We also show that the board monitoring is driven by corporate events, such as an acquisition or a restatement of financial statements. We find that board activity has a positive impact on firm value. Our results also indicate that the external pressure has had a salutary effect and recent regulations have led to some increase in firm value. A second set of proxies is based on the shift to a fully independent Audit, Compensation and Nominating Committees. We find that firms increased the independence of these Board committees following the enactment of the 2002 Sarbanes-Oxley Act.